2010
DOI: 10.1128/iai.00204-10
|View full text |Cite
|
Sign up to set email alerts
|

Conidia but Not Yeast Cells of the Fungal PathogenHistoplasma capsulatumTrigger a Type I Interferon Innate Immune Response in Murine Macrophages

Abstract: Histoplasma capsulatum is the most common cause of fungal respiratory infections and can lead to progressive disseminated infections, particularly in immunocompromised patients. Infection occurs upon inhalation of the aerosolized spores, known as conidia. Once inside the host, conidia are phagocytosed by alveolar macrophages. The conidia subsequently germinate and produce a budding yeast-like form that colonizes host macrophages and can disseminate throughout host organs and tissues. Even though conidia are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 91 publications
2
37
1
Order By: Relevance
“…Interestingly, Flt3-induced DCs release IFNs-I in response to C. albicans (11), and unmethylated CpG motifs from Aspergillus fumigatus induce IFN-a production through TLR9 activation in human DCs (12). A recent report also suggests that IFNs-I contribute to the response of mice to Cryptococcus neoformans and Histoplasma capsulatum in vivo (13,14). However, the molecular mechanisms by which Candida spp.…”
mentioning
confidence: 98%
“…Interestingly, Flt3-induced DCs release IFNs-I in response to C. albicans (11), and unmethylated CpG motifs from Aspergillus fumigatus induce IFN-a production through TLR9 activation in human DCs (12). A recent report also suggests that IFNs-I contribute to the response of mice to Cryptococcus neoformans and Histoplasma capsulatum in vivo (13,14). However, the molecular mechanisms by which Candida spp.…”
mentioning
confidence: 98%
“…Robust immune responses by APCs are thought to be driven by the cooperation of signaling pathways that emanate from each of the innate receptors (1-5). However, a given innate signaling pathway, essential against some pathogens, may be counterproductive for responses against others (4,(6)(7)(8)(9)(10)(11). Thus, although the main tenet still holds true that innate signaling pathways can engage by cooperation, complementation, and compensation to ensure effective immune responses (12), one may also envisage an additional…”
mentioning
confidence: 99%
“…In previous work, we showed that host macrophages induce different innate immune responses when infected with conidia or yeast cells (4), suggesting that macrophages recognize and respond to an unknown factor(s) that is unique to conidia. Here we describe the development of robust conditions for production and purification of Histoplasma conidia, with the goal of characterizing these cells and comparing their transcriptome to those of yeast and mycelia.…”
mentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMDM) from 8-week-old female C57BL/6 mice were obtained as previously described (4,16). BMDM were seeded at 2 ϫ 10 5 cells/well in 24-well dishes in bone marrow-derived macrophage medium and then were incubated overnight at 37°C in 5% CO 2 .…”
mentioning
confidence: 99%